Evaluating the effects of PeakATP® supplementation on visuomotor reaction time and cognitive function following high-intensity sprint exercise - Moon, Jessica M.; Dufner, Trevor J.; Wells, Adam J. (Frontiers in Nutrition, 2023)
The purpose of this study was to examine the effects of 14-days adenosine 5'-triphosphate (ATP) supplementation (PeakATP ® ) on reaction time (RT), multiple object tracking speed (MOT), mood and cognition. Twenty adults (22.3 ± 4.4 yrs., 169.9 ± 9.5 cm, 78.7 ± 14.6 kg) completed two experimental trials in a double-blind, counter-balanced, crossover design. Subjects were randomized to either PeakATP ® (400 mg) or PLA and supplemented for 14-days prior to each trial. During each trial, subjects completed a three-minute all-out test on a cycle ergometer (3MT), with measures of visuomotor RT (Dynavision D2 Proactive [Mode A] and Reactive [Mode B] tasks), MOT (Neurotracker), mood (Profile of Mood States Questionnaire; POMS) and cognition (Automated Neuropsychological Assessment Metrics; ANAM) occurring before (PRE), immediately post (IP) and 60 min post-3MT (60P). Subjects ingested an acute dose of the assigned supplement 30 min prior to completing PRE assessments for each trial. Trials were separated by a 14-day washout period. PeakATP ® significantly attenuated declines in hits (p = 0.006, ηp 2 = 0.235) and average RT (AvgRT, p = 0.006, ηp 2 = 0.236) in Mode A, significantly improved AvgRT (p = 0.039, ηp 2 = 0.174) in Mode B, and significantly reduced the total number of misses (p = 0.005, ηp 2 = 0.343) in Mode B. No differences between treatments were noted for MOT, POMS or ANAM variables. In conclusion, these results indicate that PeakATP ® maintains proactive RT and improves reactive RT following high-intensity sprint exercise suggesting that supplemental ATP may mitigate exercise induced cognitive dysfunction.